Tinjauan Yuridis terhadap Ketimpangan Pengaturan Sanksi antara Wajib Pajak dan Fiskus dalam Sengketa Pajak Berdasarkan Undang-Undang Ketentuan Umum dan Tata Cara Perpajakan: Penelitian - Julius Setiawan; Demson Tiopan; Agus Setiawan; Shelly Kurniawan (Jurnal Pustaka Cendekia Hukum dan Ilmu Sosial, 2026)
This study aimed to analyze the regulation of sanctions imposed on taxpayers and tax authorities (fiskus) in tax disputes based on the Law on General Provisions and Tax Procedures (UU KUP), as well as to examine the disparity in legal accountability between the two parties. The study employed normative legal research using statutory and conceptual approaches. Legal materials consisted of primary, secondary, and tertiary legal sources collected through library research and analyzed qualitatively using legal interpretation and legal reasoning methods. The results showed that UU KUP regulates administrative and criminal sanctions against taxpayers in a detailed and comprehensive manner, while the legal accountability and sanction mechanisms for tax authorities remain limited and are not explicitly regulated. This disparity creates an imbalance in legal protection, affects legal certainty in tax dispute resolution, and is inconsistent with the principles of equality before the law and justice. Therefore, regulatory reform is necessary to strengthen the accountability of tax authorities and establish a more balanced and equitable tax law enforcement system.